Analisis Penerjemahan Metafora: Studi Kasus Metafora Dalam Novel Yukiguni Karya Kawabata Yasunari Dan Terjemahannya Daerah Salju Oleh Ajip Rosidi - Widiarti, Rini (Lingua Cultura, 2011)
This study aims to describe the form of metaphorical translation of the source language (SL),Â Japanese, into the target language (TL), Indonesian, as well as the equivalences in TL. The study alsoÂ explains any the translation procedures used by the translator to get a natural translation so that theÂ metaphor contained in the target text is able to give the same impression with the original text. Data wereÂ collected from the work of Kawabata Yasunari â€œYukiguniâ€ Novel and the translation "Daerah Salju" byÂ Ajip Rosidi. Metaphor data were obtained by recognizing the collocation incompatibility of that theÂ referent of a word des not match common sense. The results found are TL metaphors are translated in twoÂ forms of metaphor and non metaphor. Forms of non-metaphor are divided into simile and non-figurativeÂ expression. The results showed that procedure of modulation translation plays an important role to conveyÂ the meaning of TL, especially about viewpoint changes and explicit indication. Viewpoint changes occur onÂ metaphorical imagery while explicit indication occurs at similarity points. Transposition procedure is notÂ only used to generate a natural translation in terms of language but also to divert the message from SL toÂ TL. Noted equvalences are widely used by translators to explain the concept of Japanese culture.